Candidate genes for obstructive sleep apnea in non-syndromic children with craniofacial dysmorphisms – a narrative review - Marincak Vrankova, Zuzana; Krivanek, Jan; Danek, Zdenek; Zelinka, Jiri; Brysova, Alena; Izakovicova Holla, Lydie; Hartsfield, James K.; Borilova Linhartova, Petra (Frontiers in Pediatrics, 2023)
Pediatric obstructive sleep apnea (POSA) is a complex disease with multifactorial etiopathogenesis. The presence of craniofacial dysmorphisms influencing the patency of the upper airway is considered a risk factor for POSA development. The craniofacial features associated with sleep-related breathing disorders (SRBD) – craniosynostosis, retrognathia and micrognathia, midface and maxillary hypoplasia – have high heritability and, in a less severe form, could be also found in non-syndromic children suffering from POSA. As genetic factors play a role in both POSA and craniofacial dysmorphisms, we hypothesize that some genes associated with specific craniofacial features that are involved in the development of the orofacial area may be also considered candidate genes for POSA. The genetic background of POSA in children is less explored than in adults; so far, only one genome-wide association study for POSA has been conducted; however, children with craniofacial disorders were excluded from that study. In this narrative review, we discuss syndromes that are commonly associated with severe craniofacial dysmorphisms and a high prevalence of sleep-related breathing disorders (SRBD), including POSA. We also summarized information about their genetic background and based on this, proposed 30 candidate genes for POSA affecting craniofacial development that may play a role in children with syndromes, and identified seven of these genes that were previously associated with craniofacial features risky for POSA development in non-syndromic children. The evidence-based approach supports the proposition that variants of these candidate genes could lead to POSA phenotype even in these children, and, thus, should be considered in future research in the general pediatric population.